The implementation of FRS 138 intangible assets and disclosure practices in the annual reports of Malaysian public listed companies / Normawati binti Non - Non, Normawati (2013)
The main objective of this study is to investigate on the mandatory and voluntary disclosure practices of the public listed companies in relation to the Malaysian Financial Reporting Standard (FRS) 138 Intangible Assets. Intangible assets are the main growth inducer in a knowledge economy and are becoming more important than the tangible assets. Unfortunately, the criteria and requirements set by FRS 138 resulting in many intangible assets go unrecognised. Consequently, public listed companies voluntarily provide additional intangibles-related information to educate their users of accounts and assist them in making accurate decision. However, due to the unavailability of a proper framework and guidelines on the voluntary disclosures, the type and amount of information provided vary amongst companies. This study assists the accounts preparers in identifying and understanding the areas that they lack of knowledge and appreciation on the intangible assets, and simultaneously assists the national standard setter to curb non-compliance issues. For this purpose, two disclosure models were calculated using the scores from a self-construct compliance checklist. The first model assumes an item not disclosed in the annual report as not applicable to the company, whilst the second model regards non-disclosure as non-compliant. This study found that there is a significant difference in the implementation of FRS 138 and this was due to the element of uncertainty on how to treat non-disclosed items. This study thus supports the argument by users of accounts that an annual report fails to reflect what actually transpires within the public listed company. Next, this study examines the types of information on intangibles that are normally disclosed voluntarily in the annual reports and finds out the amount of disclosures made for each type of intangibles by using thematic content analysis. It was found that companies are willing to provide their users of accounts with information beyond the requirement of FRS 138, but in general most information disclosed are historical in nature and might not contribute much in making decision for the future. This study concludes that a proper guideline is required to assist accounts preparers on the type of information to disclose and the frequency (amount) of disclosure needed so that users of account, especially the investors and analysts gain benefits from such disclosures, without exposing the public listed companies to possible threats from the competitors. Finally, this study also examines the determinants that influence the extent of compliance with FRS 138. Independent variables comprise of corporate governance factors and company-specific factors. This study suggests that all corporate governance determinants are significant in explaining the implementation practice of FRS 138. As for company-specific factors, established companies with proven financial performance on the Main market of Bursa Malaysia disclose more information compared to young and sponsored companies from the ACE market.